Changes in the permafrost environment under dual impacts of climate change and human activities in the Hola basin, northern Da Xing'anling Mountains, Northeast China. (10th April 2022) - He, Ruixia; Jin, Huijun; Luo, Dongliang; Huang, Yadong; Ma, Futing; Li, Xiaoying; Wang, Hongwei; Li, Yan; Jia, Ning; Li, Xinyu; Jin, Xiaoying; Serban, Raul‐David; et al.
Abstract: The Hola basin in the northern Da Xing'anling Mountains in Northeast China has been extensively developed for coal mining since the 1980s, resulting in a significantly degrading permafrost environment. However, the changing thermal state of permafrost under the boreal forest remains unclear. Based on ground temperature records from nine monitoring boreholes at three areas (disturbed, backfilled, and undisturbed areas) from 2015 to 2020, the thermal state of permafrost under the dual influences of climate change and human activities were evaluated. It is found that the temperatures at the depth of zero annual amplitude (TZAA ) in the disturbed area increased by 0.2–0.5°C during the past 6 years, turning the cold permafrost (TZAA ≤ −1.0°C) into a warm one (−1 ≤ TZAA ≤ 0°C). Additionally, the permafrost table was lowered by 0.8–7.0 m. As a result, subaerial supra‐permafrost talik occurred. However, TZAA in the undisturbed areas lowered by 0.03–0.11°C, possibly due to the lagged response of the local climate cooling during 2001–2010. In the meantime, TZAA rose sharply in the disturbed areas, indicating more significant influences of intense human activities on permafrost in comparison with that of climate change. As the permafrost degrades, the boreal permafrost eco‐environment has changed dramatically, as revealed by the draining and drying up of the Yueya'hu Lake in the southern Hola basin. These results help reveal the physical mechanisms, evaluate the rates and amplitudes of environmental changes, and manage the boreal forest environment and resources in a sustainable manner.